Inflammation From Peripheral Organs to the Brain: How Does Systemic Inflammation Cause Neuroinflammation? - Sun, Yuanjie; Koyama, Yoshihisa; Shimada, Shoichi (Frontiers in Aging Neuroscience, 2022)
As inflammation in the brain contributes to several neurological and psychiatric diseases, the cause of neuroinflammation is being widely studied. The causes of neuroinflammation can be roughly divided into the following domains: viral infection, autoimmune disease, inflammation from peripheral organs, mental stress, metabolic disorders, and lifestyle. In particular, the effects of neuroinflammation caused by inflammation of peripheral organs have yet unclear mechanisms. Many diseases, such as gastrointestinal inflammation, chronic obstructive pulmonary disease, rheumatoid arthritis, dermatitis, chronic fatigue syndrome, or myalgic encephalomyelitis (CFS/ME), are known to trigger neuroinflammation through several pathways. The mechanisms of action for peripheral inflammation-induced neuroinflammation include disruption of the blood-brain barrier, activation of glial cells associated with systemic immune activation, and effects on autonomic nerves via the organ-brain axis. In this review, we consider in detail previous studies on the relationship between systemic inflammation and neuroinflammation, focusing on the brain regions susceptible to inflammation.